EXPLORING INDONESIAN EFL TEACHERS’ PERSPECTIVES ON THEIR SELF-REGULATION - Wijaya, Kristian Florensio (Sanata Dharma University Yogyakarta, 2022)
AbstractThe quality of ELT enterprises is strongly determined by its teachers’ dedication and commitment to imparting meritorious educational outcomes for diverse learners. One of the affective EFL teachers’ aspects that should be paid more exhaustive attention to is self-regulation. It is theoretically grounded that highly self-regulated EFL teachers are the individuals exceptionally eager to confront various teaching-learning obstructions. This present qualitative study was conducted in the support of narrative inquiry to obtain more renewable rewarding insights from the targeted research participants based on their recited stories. To fulfill this research objectivity, 5 open-ended written narrative interview questions were addressed to 2 invited Indonesian EFL teachers experiencing quite long-range teaching experiences. The results showcased that highly self-regulated Indonesian EFL teachers had transfigured into more innovative learning facilitators and professional educators. Thus, it can be inferred that self-regulation fully allowed Indonesian EFL teachers to be more judicious decision-makers and supportive learning counselors. Some suggestions were also depicted in the closing section. Keywords: Self-regulation; EFL teachers’ perspectives; narrative inquiry